Antenatal phenotype associated with PAK2 pathogenic variants: bilateral pleural effusion as a warning sign - Louis Domenach; Caroline Rooryck; Marine Legendre; Hanane Bouchghoul; Claire Beneteau; Henri Margot (BMC Medical Genomics, 2025)
Abstract Fetal pleural effusions can arise in various contexts with different prognosis. They have been reported in fetuses presenting with hereditary or acquired conditions. One particularly rare genetic disorder, known as Knobloch syndrome, seems to emerge as a potential new cause of fetal pleural effusions, associated with severe outcomes. Knobloch syndrome 1 can be caused by biallelic variants in COL18A1. It is primarily characterized by its ophthalmic features, including severe vitreoretinal degeneration with retinal detachment and macular abnormalities. Neurological defects such as encephalocele and developmental delay, along with skeletal and renal malformations, are also associated with the syndrome. The Knobloch syndrome 2 is caused by monoallelic variants in the kinase domain of PAK2. It is less described and seems to also be associated with cardiac and respiratory damage in addition to the Knobloch syndrome 1 phenotype. PAK2 is a ubiquitous protein with a major implication in regulation and remodeling of the cytoskeleton and numerous other cellular pathways. Knobloch-associated variants seem to cause a loss of the kinase function of the protein. Even if the ophthalmic defects are almost constant, PAK2-associated Knobloch syndrome has slightly different features from Knobloch syndrome 1 in which pulmonary and lymphatic damages are still unseen. In a prenatal trio exome sequencing, we identified a novel de novo PAK2 missense variant, NM_002577.4:c.836 A > C, p.(Gln279Pro), classified as likely pathogenic in a 24 weeks of gestation fetus whose only sign was severe bilateral pleural effusion. From a literature review of patients, we recognize this sign as an important antenatal indicator of Knobloch syndrome 2, as it was the first sign identifiable in 2 out of 5 patients. This adds new evidence for the implication of this gene in fetal pleural effusions, with potentially severe outcomes.